Enhancing Reading and Writing Skills Through the Local Wisdom-Based Animated Video Media - Handayani, Winarsih; Adi, Banu Setyo (Universitas Pendidikan Indonesia, 2025)
This study investigates the impact of local wisdom-based animated video media on enhancing the reading and writing skills of first-grade students. The challenge of improving literacy skills among young learners, particularly where traditional methods may not fully engage them. Utilizing a pre-test and post-test framework, the research involved 67 students from four elementary schools. The study employs a pre-test and post-test research design, utilizing a quantitative approach to measure changes in student performance. The findings revealed a significant improvement in literacy scores, with the mean score increasing from 11.373 before exposure to the videos to 16.179 afterward. This 4.806 means difference, supported by a t-value of 19.956 and a p-value of 0.000, underscores the effectiveness of culturally relevant materials in engaging students and improving their literacy skills. The reduction in score variability after the intervention indicates a more uniform enhancement in literacy across the student population. This study advocates integrating local wisdom into educational resources, as it fosters deeper engagement, motivation, and a sense of identity among learners. The contribution of this research lies in demonstrating that culturally responsive teaching strategies can bridge the gap between home and school literacy experiences, ultimately contributing to improved academic outcomes and lifelong learning.